Do Audits Deter or Provoke Future Tax Noncompliance? : Evidence on Self-employed Taxpayers - Beer, Sebastian (IMF Working Papers; Working Paper ;, 2019)
This paper employs unique tax administrative data and operational audit information from a sample of approximately 7,500 self-employed U.S. taxpayers to investigate the effects of operational tax audits on future reporting behavior. Our estimates indicate that audits can have substantial deterrent or counter-deterrent effects. Among those taxpayers who receive an additional tax assessment, reported taxable income is estimated to be 64% higher in the first year after the audit than it would have been in the absence of the audit. In contrast, among those taxpayers who do not receive an additional tax assessment, reported taxable income is estimated to be approximately 15% lower the year after the audit than it would have been had the audit not taken place. Our results suggest that improved targeting of audits towards noncompliant taxpayers would not only yield more direct audit revenue, it would also pay dividends in terms of future tax collections.